Structure of sets of solutions of parametrised semi-linear elliptic systems on spheres. (November 2021) - Gołȩbiewska, Anna; Stefaniak, Piotr
Abstract: In this paper we study a parametrised non-cooperative symmetric semi-linear elliptic system on a sphere. Assuming that there exist critical orbits of the potential, we study the structure of the sets of solutions of the system. In particular, using the equivariant Rabinowitz alternative we formulate sufficient conditions for a bifurcation of unbounded sets of solutions.